Effect of lactic acid-rich sourdough bread on appetite regulation: A randomized, double-blind controlled trial - Georgia Chatonidi; Inés Pradal; Luc De Vuyst; Christophe M. Courtin; Kristin Verbeke (Current Research in Food Science)
Sourdough bread consumption has been associated with improved glucose and appetite regulation thanks to the presence of organic acids produced during fermentation of the flour-water mixture. We investigated the effects of whole meal sourdough bread (WSB) rich in lactic acid on energy intake, satiety, gastric emptying, glucose, and C-peptide response compared to whole meal yeast bread (WYB). Forty-four normal-weight participants (age: 30 ± 10 y; BMI: 23 ± 2 kg/m2) participated in this double-blind, randomized cross-over trial, consisting of two study visits separated by one week. During each study visit, gastric emptying, subjective appetite, glucose, and C-peptide concentrations were measured at regular time intervals over a 4-h period. After 4 h, ad-libitum energy intake was assessed. Despite no effect of bread type on ad-libitum energy intake at the subsequent meal (p = 0.068), WSB led to lower hunger (p < 0.001), higher fullness (p < 0.001), lower desire to eat (p < 0.001), and lower prospective food consumption (p < 0.001) compared to WYB. WSB had a higher gastric half-emptying time (p = 0.002), lower glucose response between 15 and 30 min (p < 0.05) after bread consumption, and lower C-peptide response between 15 and 90 min (p < 0.05) after bread consumption, compared to WYB. These findings suggest that the consumption of WSB, rich in lactic acid, acutely enhanced satiety and improved the postprandial metabolic response. However, these effects did not result in reduced ad-libitum energy intake.